THE IMPLEMENTATION OF FISCAL FINANCE BY UMAR BIN KHATAB (AN ENFORCEMENT IN INDONESIA) - Siri, Rusli; Abdullah, M. Wahyuddin; Tabe, Ridwan (Tasharruf: Journal Economics and Business of Islam, 2020)
Umar bin Khattab is a Caliph who replaced the leadership of Abu Bakar after his death. Umar bin Khattab led the people starting in the year 13 AH/ 634 AD. Poverty is decreasing and the welfare of employees is guaranteed. This research uses a descriptive qualitative method by collecting the data from books such as history books of Islamic economic thought, the historical milestone of the economic thought of Umar Bin Al Khattab, and books such as ijtihad of Umar bin Khattab. The results of this study revealed that Umar was a leader who became a role model not only in government but managing the finances of the state was also an excellent exemplar of him. Because many leaders today who carry out the fiscal policy do not consider the benefit of the people, instead enrich themselves and their colleagues in a great deal. The fiscal policy of Umar is based solely on maslahah that is in accordance with the Qur'an and Sunnah. The policy regarding the salaries of the heads of state and soldiers is a new thing. Because in the ages of the Rasulullah and Abu Bakr had never made a payroll to the Head of State and the Army. This is a sign which shows that Islamic fiscal policy in the period of Umar was more advanced.